Effect of cyproterone acetate on alpha1-adrenoceptor subtypes in rat vas deferens - Campos, M. [UNESP]; Morais, P.L. [UNESP]; Pupo, A.S. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2003)
Gonadal hormones regulate the expression of alpha1-adrenoceptor subtypes in several tissues. The present study was carried out to determine whether or not cyproterone acetate, an anti-androgenic agent, regulates the alpha1-adrenoceptor subtypes that mediate contractions of the rat vas deferens in response to noradrenaline. The actions of subtype selective alpha1-antagonists were investigated in vas deferens from control and cyproterone acetate-treated rats (10 mg/day, sc, for 7 days). Prazosin (pA2 ~9.5), phentolamine (pA2 ~8.3) and yohimbine (pA2 ~6.7) presented competitive antagonism consistent with activation of alpha1-adrenoceptors in vas deferens from both control and treated rats. The pA2 values estimated for WB 4101 (~9.5), benoxathian (~9.7), 5-methylurapidil (~8.5), indoramin (~8.7) and BMY 7378 (~6.8) indicate that alpha1A-adrenoceptors are involved in the contractions of the vas deferens from control and cyproterone acetate-treated rats. Treatment of the vas deferens from control rats with the alpha1B/alpha1D-adrenoceptor alkylating agent chloroethylclonidine had no effect on noradrenaline contractions, supporting the involvement of the alpha1A-subtype. However, this agent partially inhibited the contractions of vas deferens from cyproterone acetate-treated rats, suggesting involvement of multiple receptor subtypes. To further investigate this, the actions of WB 4101 and chloroethylclonidine were reevaluated in the vas deferens from rats treated with cyproterone acetate for 14 days. In these organs WB 4101 presented complex antagonism characterized by a Schild plot with a slope different from unity (0.65 ± 0.05). After treatment with chloroethylclonidine, the complex antagonism presented by WB 4101 was converted into classical competitive antagonism, consistent with participation of alpha1A-adrenoceptors as well as alpha1B-adrenoceptors. These results suggest that cyproterone acetate induces plasticity in the alpha1-adrenoceptor subtypes involved in the contractions of the vas deferens.
Keywords: Alpha1-adrenoceptors; Vas deferens; Cyproterone acetate